Tropheryma whipplei Endocarditis: Case Presentation and Review of the Literature. (7th December 2018) - McGee, Michael; Brienesse, Stephen; Chong, Brian; Levendel, Alexander; Lai, Katy
Abstract: Whipple's disease is a rare infective condition, classically presenting with gastrointestinal manifestations. It is increasingly recognized as an important cause of culture-negative endocarditis. We present a case of Whipple's endocarditis presenting with heart failure. A literature review identified 44 publications documenting 169 patients with Whipple's endocarditis. The average age was 57.1 years. There is a clear sex predominance, with 85% of cases being male. Presenting symptoms were primarily articular involvement (52%) and heart failure (41%). In the majority of cases, the diagnosis was made on examination of valvular tissue. Preexisting valvular abnormalities were reported in 21%. The aortic valve was most commonly involved, and multiple valves were involved in 64% and 23% of cases, respectively. Antibiotic therapy was widely varied and included a ceftriaxone, trimethoprim, and sulfamethoxazole combination. The average follow-up was 20 months, and mortality was approximately 24%. Physician awareness is paramount in the diagnosis and management of this rare condition.